Six steps for a successful phacoemulsification in hard cataracts - S Venkatesh; Mavnika; Shruti P Hedge (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2021)
Phacoemulsification in rock-hard cataracts is always challenging for the phaco surgeon. Patient presenting with hard cataract is common in rural and suburban areas. In such situations phaco surgeons face higher incidence of significant complication like endothelial cell loss, posterior capsular rupture, zonular dialysis. By judicious use of the appropriate technology like perfect power modulations, enhanced fluidics, adequate OVDs usage better results can be achieved in these cases. In this short communication we have put together six salient steps that would help the surgeon in achieving successful phacoemulsification in hard cataracts.